Emerging Therapies in Respiratory Tract Infections: Current Advances and Future Perspectives - Abhishek Kumar; Pankaj Chasta; Kamalesh Mistry (Recent Trends in Infectious Diseases, 2025)
The impact of respiratory tract infections (RTI) as a global public health problem continues to be high morbidity and mortality rates. The development of novel therapeutic approaches stemmed from the fact that conventional treatment strategies, antibiotics, antivirals, antifungals etc. have become increasingly ineffective because of rise of antimicrobial resistance (AMR). Next generation therapies, such as novel antimicrobial agents, host directed therapies and novel drug delivery systems have come on the stage by recent development in biotechnology and nanomedicine. Respiratory pathogens have demonstrated promising efficacy through the emergence or the pursuit of mRNA based antivirals, CRISPR-based gene editing and monoclonal antibodies. Inhalable nanocarriers, liposomal formulations, and bioengineered hydrogels improved drug targeting and bioavailability, and provided site specific treatment with minimal systemic toxicity. Besides that, gene therapy and RNA based therapeutics including siRNA, antisense oligonucleotides have also further expanded treatable entity for chronic RTIs. Nevertheless, efforts will have to be made to overcome regulatory hurdles, ethical concerns and clinical translation barriers before the adoption is widespread. Furthermore, artificial intelligence and big data analytics are benefiting to optimize the treatment strategies and thus to follow the personalized medicine. This review covers in a comprehensive manner recently developed drugs for RTI management including innovative drug delivery systems, gene-based therapeutics and host directed therapies. Integrating multidisciplinary approaches at the early stage for overcoming resistance mechanisms and to develop more effective and personalized interventions is the future of RTI treatment.
Keywords: Gene therapy; Inhalable Drug Delivery; Nanomedicine; RNA-Based Therapeutics; Respiratory Tract Infections; antimicrobial resistance